A study on the perceptions of librarians and staff on the impact of technology on the organization and personnel of selected academic libraries in CALABARZON - Torres, Efren M., Jr.; Cabbab, Johann Frederick A.; Mallari, Florenda D.; Faderon, Rosalie B. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2002)
New technologies are now a part of everyday life, with the majority of daily activities revolving around the use of computers. Truly, information professionals and workers have been impacted by the rapid changes in technology in years. A review of the literature revealed little research studies that have been conducted to investigate the impact of technology on the organization and personnel level locally. Therefore, the purpose of this study was to find out how the librarians and staff from selected academic libraries in CALABARZON perceive the impacts of technology in their workplace.
A census of 171 librarians and paraprofessional staff was selected to participate in the study, and a total of 145 questionnaires were returned resulting in 84.79 percent response rate. Of the completed questionnaires, 52 are librarians and 93 are paraprofessional staff. Respondents came from the selected academic libraries, namely: De La Salle University-Dasmariñas (DLSU-D), De La Salle Health Sciences Institute (DLSHSI), Adventist International Institute of Advanced Studies (AIIAS), De La Salle Lipa (DLS-L), Lyceum of Batangas, University of the Philippines Los Baños (UPLB), University of Perpetual Help Laguna-Biñan (UPHL-B), Manuel S. Enverga University Foundation (MSEUF) and Sacred Heart College.
The data gathered from the survey questionnaires revealed that in terms of demographics, respondents with age 21-30 (27-58) comprise the most number. The sample was predominantly female (75.86) and indicated their civil status as married (59.31). The largest group of the respondents indicated that they had been working in the library for 15 years and above (42.76), their highest educational degree obtained was the bachelor's degree (44.14) and the library department they belong to is the reader's services (53.10)
The study also found out that both librarians and paraprofessional staff react positively to the impact of technology. More staff are now starting to realize their importance as part of the decision-making process. However, there is still a need to increase staff participation and awareness in technological planning.
The findings also revealed that there is a significant relationship between library automation and changes in the organizational structure. Likewise, a significant relationship was also found out between the provision for staff training program and adequacy and quality of training received.
Librarians and staff ranked library integrated systems, the Internet, database and webpage creation, and computer hardware and software as top priorities in terms of topics under skills training and development. On the other hand, under personal development, total quality improvement, building teamwork, motivating employees, planning and organizing, diversity in the workplace and interpersonal communication are their primary topics for training. Recommendations included are the following: increase awareness on the new technologies by reading, discussing and publishing IT-related issues and experiences; raise libraries' budget to acquire IT hardware, software and collections; prioritize training and development based on the real needs of the staff.
Vita.
Special Problem (Master of Library and Information Science)
Keywords: Librarians -- Information technology -- Philippines -- CALABARZON; Library employees -- Philippines -- CALABARZON; Academic librarians -- Philippines -- CALABARZON